VIDEO EXPLAINER LOMBA CERDAS CERMAT BUNKASAI PGMP JABODETABEK 2024 - Lambok Rommy Sulaeman,; Ade Oki Pebiansyah,; Rizaldi Putra,; Memet Sanjaya,; Deni Utama,; Salsabilla Khoirun Nissa, (JURNAL PENGABDIAN MANDIRI, 2025)
In the digital era, adaptive learning media is a major necessity, especially during the pandemic, when online learning is the main solution. Learning media plays an important role in conveying messages in an attractive manner to increase students' interest, attention, and understanding. One of the challenges faced is how to effectively present Japanese culture learning materials to participants of the Bunkasai PGMP Quiz Competition (LCC) Jabodetabek, considering that conventional methods are often considered monotonous and less motivating. Digitalisation of learning through explainer videos is an innovative solution to this challenge. Explainer videos allow the presentation of complex information visually and interactively, with clear narration and attractive visuals. This research aims to develop explainer video-based learning media to support the preparation of LCC Bunkasai 2024 participants. The approach used is the ADDIE development model, including needs analysis, content design, video development, implementation, and evaluation. The results showed that the use of explainer videos improved students' motivation and understanding of Japanese culture, with comprehension scores increasing by 30% after learning. Teachers and participants gave positive feedback regarding the effectiveness and attractiveness of this media. The video explainer also provides flexibility of access, allowing students to learn at their own pace. In conclusion, digitisation of learning through explainer videos proved to be effective and relevant for the younger generation. This media not only supports competitive learning at LCC, but also has the potential to be applied more widely in cultural education. Further development is proposed to cover more in-depth Japanese cultural topics, in order to broaden the scope of learning and its educational impact